Getting to Know Local Tubers from the School Environment: An Analysis of Elementary School Students' Recognition and Appreciation in Malang City - Nurinda Zulinar Rahmawati (Journal of Academic Biology and Biology Education, 2024)
Purpose of the study: This study aimed to analyze the influence of school location on elementary students’ recognition of local tuber diversity and to evaluate the appreciation of 117 elementary school students in Malang City toward processed local tuber products as an effort to strengthen local food literacy among young learners. Methodology: Descriptive research design involving 117 fourth- and fifth-grade elementary students from three schools in Malang City. Data were collected using Questionnaire I and Questionnaire II, direct tuber observation, organoleptic testing, product demonstrations, Likert scale assessment, Kruskal-Wallis test, Mann-Whitney test, descriptive statistical analysis, and Statistical Package for the Social Sciences version 16.00 for Windows. Main Findings: School location influenced students’ direct recognition of local tubers, with students near traditional markets showing higher familiarity. Pocket money profiles did not significantly affect recognition or consumption experience. Consumption of processed local tuber products was relatively equal across schools. Students’ acceptance levels varied, with generally moderate appreciation, indicating that product appearance, taste, and innovation remain important factors affecting acceptance. Novelty/Originality of this study: This study integrates assessment of elementary students’ recognition of twelve local tuber varieties with evaluation of appreciation toward processed products across different school locations. It provides new evidence that geographical school context has greater influence than economic indicators on local food recognition, offering practical insights for strengthening food education and local biodiversity conservation strategies.